NILAI BUDAYA PADA KESENIAN TRADISIONAL SISINGAAN SEBAGAI SUMBER PEMBELAJARAN IPS (Studi Deskriptif pada Lingkung Seni Mutiara Surya Putra Desa Sumber Sari Kecamatan Ciparay Kabupaten Bandung) - Prida Aprilia, - (2020)
ABSTRACT The problem in this study is there are still many educators who have not maximized the use of environment-based learning resources around students, the learning resources used by teachers are still limited to learning that is fixated on textbooks. Which is the use of cultural value-based learning resources in traditional arts, which are rarely used by educators. The purpose of this study is to find out what cultural milestones exist in the traditional art of Sisingaan in Sumber Sar Village, to identify how the community's efforts are in Sumber Sari Village Sumber Village Sari and to analyze how to integrate cultural values in the traditional arts of Sisingaan in Sumber Sari Village with Social Studies learning resources. This research is a descriptive study conducted in Sumber Sarı Village, Ciparay Subdistrict, Bandung Regency. The technique used for data collection is observation, interview, and documentation. The result of this search indicate that cultural values in Sisingaan traditional art are local values, religious values, mutual assistance values, aesthetic value and historical value. The efforts of Sumber Sari village community in preserving cultural values in the traditional art of Sisingaan is by continuing to carry out traditional art activities of Sisingaan. creative in developing Sisingaan traditional arts. Cultural values contained in the arts can be used as a source of social studies learning in some social studies learning materials in schools. Social studies learning material that is suitable and relevant to the cultural values of traditional arts of Sisingaan, namely material on the dynamics of the Indonesian population(Ethnic and Cultural diversity), Hindu- Biddhist (Hindu-Buddhist influence on Indonesia society), the plurality of Indonesia Indonesia society and integration and community life during the Islamic era (the infulence of Islam on Indonesian society). Key words: Cultural values, Sisingaan traditional art, social study learning source.